Measurement of diastolic closure rate of normal mitral valve. Issue 5 (May 1975) - Rodger, J C; Sumner, D J
Abstract : Published values for the diastolic closure rate of the normalmitral vary and reflect diffference in methods of recording and measurement. From strip chart records it was concluded that the form of the recorded mitral diastolic closure slope can vary, that reproducible measurements of the closure rate can be made from echograms in which diastolic closure approximates closely to a monophasic form, that the amplitude of these echograms is maximal, and that their closure movements remain essentially monophasic at chart speeds up to 100 mm/s. Measuring only complexes with essentially monophasic closure movements, the within and between-subjected variation of the normal mitral diastolic closure rate was investigated. The ranges obtained from multiple measurements in a single subject and from a group of 45 normal subjects were comparable but the distribution of the results differed. It was concluded that there was a real between-subject variation in the normal mitral diastolic closure rate and that the diastolic closure rate in a single subject should be determined by measurement of a series of complexes. The accuracy of measurement of the diastolic closure rate of the normal mitral valve has been improved by using strip chart records and by measuring only echograms in which diastolic closure approximates closely to a monophasic form.